Kształt i charakter lokalnego serwisu informacyjnego na przykładzie „Łódzkich Wiadomości Dnia” - Grzegorzewski, Krzysztof (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2015)
The paper contains an analysis of a highly popular regional daily TV news program called “Łódzkie Wiadomości Dnia” (Daily News from Lodz), emitted and produced by channel TVP Łódź. The author carried out precise quantitative and qualitative research based on the programs emitted during one full week. The character of the program proved to be different than that of nationwide and international TV news magazines, and contained more social and practical information for the average viewer (about infrastructure, ordinary people and their problems, cultural events in Łódź and in the surounding region). The editors try to avoid hard political news and controversies, usually remaining closer to infotainment and politainment. The selection of news and topics benefits the program and results in the high quality of this regional TV news magazine.